Underlying Small Vessel Disease Associated With Mixed Cerebral Microbleeds - Blanc, Clemence; Viguier, Alain; Calviere, Lionel; Planton, Mélanie; Albucher, Jean François; Rousseau, Vanessa; Sommet, Agnès; Bonneville, Fabrice; Pariente, Jérémie; Olivot, Jean Marc; Raposo, Nicolas (Frontiers in Neurology, 2019)
Background and Purpose: Whether patients with both lobar and deep cerebral microbleeds (mixed CMB) have advanced cerebral amyloid angiopathy (CAA), hypertensive angiopathy (HA) or both is uncertain. To get insight into the underlying small vessel disease (SVD) associated with mixed CMB, we explored its association with cortical superficial siderosis (cSS), a key marker of CAA and other MRI markers of SVD in patients with intracerebral hemorrhage (ICH). Methods: Of 425 consecutive patients with acute ICH who had received brain MRIs, 260 had ≥1 CMB and were included in the analysis. They were categorized as strictly lobar CMB (suggesting CAA), strictly deep CMB (suggesting HA) or mixed CMB. Clinical and imaging characteristics were compared (1) between the three CMB groups and (2) within mixed CMB patients according to the symptomatic ICH location. Results: Overall, 111 (26%) patients had mixed CMB. Compared to strictly lobar CMB (n = 111) and strictly deep CMB (n = 38), patients with mixed CMB had a more severe burden of lacune, white matter hyperintensities and CMB. cSS was observed in 24.3% of patients with mixed CMB compared to 44.1% in strictly lobar CMB and 10.5% in strictly deep CMB (p < 0.0001). Among patients with mixed CMB, 44 (39.6%) had a lobar symptomatic ICH and 67 (60.4%) had a non-lobar ICH. Patients with non-lobar ICH were more likely to have hypertension, whereas those with lobar ICH were more likely to have cSS and chronic lobar ICH and had higher ratio lobar CMB count/total CMB count. Conclusions: Mixed CMB is frequently encountered in patients with ICH and appears as a heterogeneous group, suggesting that both CAA and HA may be contributing to mixed CMB. Neuroimaging markers including ICH location, cSS, and CMB distribution may indicate the predominant underlying vasculopathy, with potential prognostic implications.